Bill Viola : o tempo em suspensão - Grando, Angela (2019)
Within the general field of video artist Bill Viola’s work, we propose an approach to the relationship between a visible energy in his videographic image, invested with some kind of “fragment of an existential memory”, and the mnemonic image of Aby Warburg, invested with a complex temporality and extended from his reference of the past and his symptomatic future, perpetuated in one cultural memory